THE INFLUENCE OF PRINCIPALS' VISIONARY LEADERSHIP AND PEDAGOGICAL COMPETENCE ON THE WORK EFFECTIVENESS OF PUBLIC ELEMENTARY SCHOOL TEACHERS - YULIAANTI, Lia (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2025)
The purpose of this study is to investigate: (1) The Influence of Visionary Leadership of the Principal on the Work Effectiveness of State Elementary School Teachers in Cluster 4 of Tangerang District; (2) The Effect of Pedagogic Competence on the Work Effectiveness of State Elementary School Teachers in Cluster 4, Tangerang District; (3) The principal's supervision of the Pedagogic Competence of State Elementary School Teachers in Cluster 4 of Tangerang District. This research is a type of correlational research. The approach used in this study uses a quantitative approach. The population in this study was 150 teachers in State Elementary School Teachers in Cluster 4, Tangerang District, totaling 109 teachers sample who were randomly sampled. The analysis technique used is path analysis technique. Based on the results of the analysis, it is known that: (1) There is a direct positive and significant influence of the principal's visionary leadership on the effectiveness of the work of state elementary school teachers in Cluster 4 of Tangerang District. (2) There is a direct positive and significant influence of pedagogic competence on the effectiveness of the work of state elementary school teachers in Cluster 4 of Tangerang District. (3) There is a direct positive and significant influence of the principal's visionary leadership on the pedagogical competence of State Elementary School teachers in Cluster 4 of Tangerang District.